Association between receiving the Aksi Bergizi Social Behavioral Change Communication (SBCC) intervention and hygiene behaviors among secondary school students in Padang, Indonesia - Nindrea, Ricvan Dana; Wichaidit, Wit (PeerJ, 2025)
Background The Government of Indonesia and UNICEF introduced the Aksi Bergizi Social Behavioral Change Communication (SBCC) intervention to promote healthy eating and hygiene behaviors among adolescents. However, no systematic assessment of the program’s effect has been made. This study aims to assess the association between exposure to the Aksi Bergizi nutrition promotion program and hand, oral, and nail hygiene behaviors among secondary school students in Padang, Indonesia. Methods We conducted a school-based cross-sectional study in Padang Municipality, Indonesia, collecting data from 253 students attending Aksi Bergizi target schools and 253 students from non-target schools using a self-administered questionnaire. We compared hygiene behaviors between students in the two groups using descriptive statistics and multivariable logistic regression with adjustment for demographic and socioeconomic characteristics. Results All students reported brushing their teeth at least twice per day, so there was no observable difference regarding oral hygiene. However, we found that students in target schools were significantly more likely than those in non-target schools to always use soap when washing their hands both before eating (75% vs. 21%; Adjusted odds ratio (OR) = 6.03; 95% confidence interval (CI) [3.96–9.19]) and after using the toilet (74% vs. 21%; Adjusted OR = 5.74, 95% CI [3.78–8.72]). However, there was no statistically significant difference with regard to nail hygiene, i.e., cutting nails at least once per week. Conclusion We found differences between target and non-target schools regarding self-reported handwashing but no differences in nail-clipping. The findings of this study have implications for stakeholders in infectious diseases and nutrition. Future studies should consider ways to reduce social desirability bias and increase the generalizability of the study findings.
Keywords: Adolescent; Hygiene behaviors; Health education